Back to our roots or sowing new seeds: thinking anew on the paradigms of health, harm and disease. (21st November 2022) - van Schalkwyk, May C I; Zenone, Marco; Maani, Nason; Petticrew, Mark; McKee, Martin
Abstract: Health, harms and disease are intimately linked, and their promotion and distribution are determined by the social, political and physical worlds in which people live. Yet, the popular narrative on health is still dominated by a biological model that focuses on a disease-causing 'pathogen' or 'agent' that leads to pathology which is diagnosable and amenable to intervention at the individual level via measures delivered through the health care and public health systems. This model generally rests on understanding populations as a collection of individuals, with the pattern of disease seen as the sum of a series of risk factors acting on each of them. Too little attention is paid to the ways in which health, harm, disease, causation and risk are conceptualized and used as guiding concepts in research, policy debates and other fora. We often overlook the distribution of health and the regulatory regimes, norms, values and rights that promote or undermine health. By challenging our ways of thinking about health, harms and disease, we can start to appreciate with greater depth the ways in which health can be threatened and what should be seen as harmful, and conversely, opportunities for moving our systems towards promoting and protecting health.